Partisipasi Masyarakat terhadap Pengembangan Desa Wisata “Watu Rumpuk” Desa Mendak Kecamatan Dagangan Kabupaten Madiun - Hilman, Yusuf; Aziz, Muhammad Saeful Abdul (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
Tourism is important sectors which became one of the fields of economic society, Assess the potential was necessary to sustain an effort so that the sector can move all levels of society, And the participation of the possible significantly. The qualitative method descriptive was used in the study, to interpreting the data obtained in the field. The results of research to explain the management of tourist village in Mendak village either on tourism and the tourism potential climbing Tapak Bima should involve the community from management planning. t is one of the rural development community-based tourism is the responsibility of the community for potential and tourism objects that in the management of tourist village in the village mendak, they must be involved in the process of planning, implementation, and evaluation. Community involvement in the process of planning, of the project up to evaluation will encourage a sense of belonging and about the potential of tourism objects that will guarantee sustainability, potentials, and the object.